Are Sunk Costs Irrelevant? Evidence from Playing Time in the National Basketball Association - Daniel Leeds; Michael A. Leeds; Akira Motomura (Institute for the Study of Labor (IZA), 2013)
The relevance of sunk costs in decision making is one of the major sources of disagreement between neoclassical economists and behavioral economists. We test the importance of sunk costs by examining the role of a player's draft position on his playing time in the National Basketball Association. Specifically, we ask whether players taken as lottery picks or in the first round of the draft are treated differently from otherwise identical players who are chosen later. We build on previous studies in three ways. First, we study a time period that had a stronger contrast between the financial commitment to first and second-round draft picks. Second, we use a better measure of playing time by accounting fully for the time a player loses to injury, suspension, or other exogenous factor. Finally and most importantly, we use a more sophisticated methodology regression discontinuity to test for whether teams treat lottery picks or first-round picks differently from later picks. Our results find little or no impact of draft round or lottery status on playing time. Hence, our findings strongly support the neoclassical outlook.
Keywords: D03; J23; L83; 330; sunk costs; behavioral economics; basketball; regression discontinuity